Who cares about sanctions? Observations from annual reports of European firms - Denis Davydov; Jukka Sihvonen; Laura Solanko (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
This paper uses textual analysis to examine how European corporations assess sanctions in their annual reports. Using observations from a panel of almost 11,500 corporate annual reports from 2014-2017, we document significant cross-country variation in how firms perceive Russia-related sanctions. Even after controlling for firm-level characteristics, cross-country differences remain for sentiments about sanctions and contexts in which sanctions are mentioned. We also examine the role of macroeconomic linkages in explaining these differences. We show that the Russia's inward and outward FDI stocks and high levels of imports and exports with Russia only partially explain the cross-country variation, leaving a nontrivial share of variation unexplained.
URN:NBN:fi:bof-202104201183
Keywords: D22; F51; 330; sanctions; textual analysis; European firms; annual reports